Transformative Modernisation of Islamic Education Management: An Integrative-Transformative Quality-Based Management Model - Fathor Rachman; Muhammad Nihwan; Durhan Durhan; Rosidi Bahri (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
The quality of Islamic education management has been significantly constrained by managerial and leadership factors, which affect all dimensions of Islamic educational institutions. Islamic education development has often proceeded without systematic design and has not been managed in an excellent and modern manner, resulting in insufficient dynamism, relevance, professionalism, and competitiveness. This study examines the transformative modernisation framework developed by Prof. Dr KH. Muhammad Tholhah Hasan, demonstrating that Islamic educational institutions can become centres of excellence with high competitiveness when their management is developed through modern approaches. This qualitative research employs an individual life history approach combined with library research, utilising observation, interviews, documentation, and a comprehensive literature review as data collection methods. Data analysis employed domain, taxonomic, componential, cultural theme, and constant comparative analyses. The findings reveal five fundamental dimensions: (1) the concept of Islamic education management development encompasses theo-centric humanism, generating humanistic-ethical and pragmatic-empirical education models that integrate spirituality-morality with intellectuality-professionalism; (2) the foundation is based on theological, philosophical, sociological, psychological, and scientific principles; (3) the model employs spirituality atmosphere-organized work-based management through religious-modernistic and dynamic-humanistic educational management; (4) leadership combines vanguard and transformative-religious-populist characteristics; and (5) modernization is achieved through strengthening Islamic values, structural and cultural transformation, and quality enhancement. These findings synthesise into an Integrative-Transformative Quality-Based Islamic Education Management model, offering practical implications for educational institutions, policymakers, and researchers seeking to advance Islamic education management in response to contemporary challenges while maintaining authentic Islamic values.